A NEW DEVELOPMENT OF AN X–R CONTROL CHART OPTIMIZED WITH TAGUCHI, TAGUCHI-PARETO AND TAGUCHI-ABC METHODS FOR MAINTENANCE RELIABILITY OPTIMIZATION - Oluwo, Adeyinka; Alozie, Nehemiah Sabinus; Ogunmola, Bayo Yemisi; Raji, Akinwale Olusegun; Rajan, John; Jose, Swaminathan; Oke, Sunday Ayoola; Aderibigbe, Samuel Bolaji (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2026)
This paper aims to develop a variable control chart-based (R chart and X bar) method to determine the stability and predictability of the maintenance reliability parameters in a grain-based food processing plant in Nigeria. The R chart and X bar charts were developed using the changes in the range and average of reliability parameters over the maintenance period. The previous study, which is extended here, evaluates reliability parameters for 35 weeks to capture the plant's frequency of failure, MTTR, MTTF, and downtime. These are transformed into the Weibull probability density function, cumulative density function, reliability, and hazard rate and measured from the viewpoint of orthogonal array generation and analysis. This paper found that the variable control chart–based method provides an expression for the stability and prediction of the maintenance reliability parameters using Taguchi-based methods. The proposed approach would be valuable for maintenance managers to understand the behavior of their system parameters in attaining sustainable practices in the grain-based food industry. This study analyses the interactions of the maintenance reliability parameters in the grain-based food industries, which is new in the food equipment maintenance domain of practice. The originality and novelty of this approach will aid in establishing controls while ensuring that maintenance costs are minimized.